Good Governance in Cambodia: A Case Study of Khan Boeng Keng Kang, Phnom Penh - HING, Kimleng; VANN, Chandara; ROS, Ravuth; DY, Putheara (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This research study uses documentary techniques to thoroughly investigate the principles and strategies of effective governance in Boeung Keng Kang District in Phnom Penh. The research thoroughly examines different aspects of governance, like district leaders' duties, accomplishments, ongoing obstacles, strategic goals, and suggestions to improve governance effectiveness, using established documents, government reports, and official publications. By systematically analyzing these documents, the study reveals the crucial role of essential governance principles like participatory decision-making, adherence to the rule of law, transparency, fairness, accountability, and strategic vision in promoting local development and dealing with new challenges. This method allows for a comprehensive examination of the governance environment in Boeung Keng Kang District, offering a valuable understanding of the factors influencing governance behaviors among residents.